Implementation of Active Learning Methods in Islamic Elementary School/Implementasi Metode Active Learning di Madrasah Ibtidaiyah - Abd Hamid; Asrori Asrori; Rusman Rusman (STAI Ma'had Aly Al-Hikam Malang, 2022)
The purpose of this study was to determine: (1) the ability of educators to apply the active learning method, (2) the activities of educators during the application of the active learning method, (3) the activities of students during the application of the active learning method and (4) student learning outcomes, during the application of the active learning method. The results showed that: (1) The ability of educators to manage learning methods in the first cycle was 2.41 for the second cycle increased to 2.93 and in the third cycle increased again to 3.00. So for three cycles there was an increase from cycle I, cycle II, and cycle III with good categories, (2) the activity of educators in the first cycle of material delivery activities was 34.33%. In the second cycle the dominant activity decreased to 22.33% while in the third cycle the dominant activity of educators was to provide guided training by 24.33%, (3) the student activity in the first cycle was 36.67%, the second cycle decreased to 26.67% until the third cycle. . the cycle decreased again to 23.33 so that for three cycles in general there was an increase, and (4) the learning mastery of classical students in the application of learning in the first cycle 60 to the second cycle increased to 88.89% and in the first cycle increased to 88.89 cycle II III has been achieved.